Development and validation of an inverse method for identification of thermal characteristics of a short laser pulse - Łapka Piotr; Pietrak Karol; Kujawińska Małgorzata; Malesa Marcin; Oniszk Łukasz (MATEC Web of Conferences, 2018)
The paper presents development and validation of an inverse method for the identification of thermal characteristics of a short single laser pulse which stroke in a metal sample. The inverse method was applied to find unknown power of the laser pulse, the dimensionless shape parameter of the super-Gaussian function which describes the beam spatial profile as well as beginning and end times of the exposition of the metal sample to the laser pulse. The proposed inverse algorithm was based on the Levenberg-Marquardt technique as well as on temporal and spatial distributions of temperature on the rear surface of the sample, i.e., the opposite to the irradiated one, measured using the experimental stand. The performed investigations showed that the problem was ill-posed but good accuracy was obtained. The low sensitivity of registered temperature to changes in both power and duration of the pulse affected the retrieving accuracy most significantly. Moreover, the dependence of solution of the inverse problem on the initial guess was observed. The accuracy was also affected by low temporal resolution (500 Hz, with the exposure time from 0.2 to 1 ms) of the IR camera. This resolution affected the temporal sampling of measured temperatures. Despite these problems, the method was able to retrieve unknown pulse parameters with 20-25% accuracy.